2013
DOI: 10.1128/aac.00023-13
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Efficacy of β-Lactams against Replicating and Slowly Growing/Nonreplicating Mycobacterium tuberculosis

Abstract: Beta-lactams, in combination with beta-lactamase inhibitors, are reported to have activity against Mycobacterium tuberculosis bacteria growing in broth, as well as inside the human macrophage. We tested representative beta-lactams belonging to 3 different classes for activity against replicating M. tuberculosis in broth and nonreplicating M. tuberculosis under hypoxia, as well as against streptomycin-starved M. tuberculosis strain 18b (ss18b) in the presence or absence of clavulanate. Most of the combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 23 publications
3
70
0
2
Order By: Relevance
“…Determination of bacterial loads on day 9 revealed a modest but significant reduction in the bacterial load only in the case of mice that had been treated with the combination of faropenem, clavulanate, and probenecid (P Ͻ 0.05, Mann-Whitney test). This reduction in bacterial load was comparable to the decrease observed in previous studies evaluating ␤-lactams against M. tuberculosis in the mouse model (14,15,40) (Fig. 3; Table 3).…”
Section: Es E+p E+ssupporting
confidence: 74%
“…Determination of bacterial loads on day 9 revealed a modest but significant reduction in the bacterial load only in the case of mice that had been treated with the combination of faropenem, clavulanate, and probenecid (P Ͻ 0.05, Mann-Whitney test). This reduction in bacterial load was comparable to the decrease observed in previous studies evaluating ␤-lactams against M. tuberculosis in the mouse model (14,15,40) (Fig. 3; Table 3).…”
Section: Es E+p E+ssupporting
confidence: 74%
“…We determined the effects of combining AZD5847 with several TB drugs through the use of a checkerboard titration, which has been previously described (17). Briefly, using 96-well microtiter plates, we diluted one drug vertically (rows A to H) and a second drug horizontally (columns 1 to 10) to obtain various combinations of the two drugs in a final volume of 100 l for each well.…”
Section: Methodsmentioning
confidence: 99%
“…We then added to each well 100 l of H37Rv-infected 7H9 to provide an inoculum of approximately 5 ϫ 10 5 CFU/ml. The plates were incubated for 7 days, and the MIC was interpreted as described earlier (17). To evaluate whether the paired combinations of agents had additive efficacy in inhibiting M. tuberculosis (i.e., no interaction) or inhibitory efficacy more or less than the sum of their effects alone (synergy versus antagonism), we calculated the fractional inhibitory concentration index (⌺FIC) using the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…They are poor substrates for BlaC and are not affected by its ␤-lactamase activity (5). Recent reports have demonstrated that carbapenems exhibit high antimicrobial potency against M. tuberculosis; therefore, they may be considered for treatment of tuberculosis (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%